2021
DOI: 10.1021/acsami.0c22317
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Air Epoxidation of Mixed Biolefins over a Spherical Bimetal ZnCo-MOF Catalyst

Abstract: Here, we report the synthesis of spherical bimetal ZnCo-MOF materials by a hydrothermal rotacrystallization method and their catalytic activity on the air epoxidation of mixed biolefins enhanced by microwaves. The structural and chemical properties of the ZnCo-MOF materials were fully characterized by XRD, IR, SEM, TG, XPS, and NH 3 -TPD. The morphology of the material exhibited a three-dimensional spherical structure. From an NH 3 -TPD test of the ZnCo-MOF catalyst, it could be concluded that the Zn 0.1 Co 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Furthermore, chemisorption of Zn 0.75 Mg 0.25 -MOF-74 CO 2 and NH 3 was proceeded by TPD to reveal its basicity and acidity, which would play important roles in the subsequent cycloaddition reaction of CO 2 and epoxides. As shown in Figure c, there appeared NH 3 weak adsorption peaks below 300 °C, proving the presence of weak-to-medium acid sites contributed from Zn and Mg metal sites in the catalyst. , In terms of CO 2 -TPD, the weak desorption peak below 150 °C was attributed to CO 2 adsorption on unsaturated coordinated Zn 2+ and Mg 2+ . The other desorption peak over 250 °C was assigned to the medium basic sites coming from O atoms of metal oxygen pairs (Zn–O and Mg–O) in Zn 0.75 Mg 0.25 -MOF-74. , Thus, both Lewis acid sites (Zn and Mg metals) and Lewis basic sites (O atoms of metal oxygen pairs) existed in Zn 0.75 Mg 0.25 -MOF-74, facilitating its catalytic activity in the subsequent cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, chemisorption of Zn 0.75 Mg 0.25 -MOF-74 CO 2 and NH 3 was proceeded by TPD to reveal its basicity and acidity, which would play important roles in the subsequent cycloaddition reaction of CO 2 and epoxides. As shown in Figure c, there appeared NH 3 weak adsorption peaks below 300 °C, proving the presence of weak-to-medium acid sites contributed from Zn and Mg metal sites in the catalyst. , In terms of CO 2 -TPD, the weak desorption peak below 150 °C was attributed to CO 2 adsorption on unsaturated coordinated Zn 2+ and Mg 2+ . The other desorption peak over 250 °C was assigned to the medium basic sites coming from O atoms of metal oxygen pairs (Zn–O and Mg–O) in Zn 0.75 Mg 0.25 -MOF-74. , Thus, both Lewis acid sites (Zn and Mg metals) and Lewis basic sites (O atoms of metal oxygen pairs) existed in Zn 0.75 Mg 0.25 -MOF-74, facilitating its catalytic activity in the subsequent cycloaddition reaction.…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure 6c, there appeared NH 3 weak adsorption peaks below 300 °C, proving the presence of weak-to-medium acid sites contributed from Zn and Mg metal sites in the catalyst. 31,47 In terms of CO 2 -TPD, the weak desorption peak below 150 °C was attributed to CO 2 adsorption on unsaturated coordinated Zn 2+ and Mg 2+ . 48 The other desorption peak over 250 °C was assigned to the medium basic sites coming from O atoms of metal oxygen pairs (Zn−O and Mg−O) in Zn 0.75 Mg 0.25 -MOF-74.…”
Section: Resultsmentioning
confidence: 99%
“…However, with an increase of the molecular size and steric hindrance of epoxy compounds (entries 4 and 5), conversion of the corresponding cyclic carbonates decreased slightly. Nevertheless, styrene oxide as a bulky substrate showed a moderate conversion of 97% within 4 h. However, as seen in Table S3, NUC-42a displayed a higher catalytic performance than the previously documented monometallic Zn- or In-MOF catalysts because of its active {InZn} cluster and moderate channel dimensions, which could synergistically facilitate the progress of catalysis and molecular transport during the cycloaddition reaction. In addition, the 1 H NMR spectra for all of the cycloaddition products are given in Figures S8–S12.…”
Section: Resultsmentioning
confidence: 99%
“…The design and synthesis of porous metal–organic frameworks (MOFs) have aroused great attention because of their promising application in a series of regions, such as polytypic catalysis, fluorescence sensing, drug delivery, gas separation/storage, magnetism, optoelectronics, and so on. Since the first report of MOF-catalyzed cycloaddition by Han et al, there have been a lot of studies on CO 2 cycloaddition catalyzed by various MOFs, which are differentiated by their constituents and connectivities. In terms of documented references, indium-based organic frameworks (In-OFs) have become a basically reliable heterogeneous catalyst because of the unique traits of In 3+ ion including accessible high-level p orbitals, diverse coordination numbers, and distinctive electronic configurations, which render them the ability to serve as facile Lewis acid sites to activate the involved reactants of CO 2 and epoxides during the chemical conversion of epoxides to cyclocarbonates. Moreover, in the past few years, zinc-based MOFs (Zn-MOFs) with well-ordered structures or networks are also well developed for a confirmed high catalytic performance on the chemical fixation of CO 2 under mild solvent-free conditions because of their moderate Lewis acidity and affinity to CO 2 and epoxide molecules from 3d 10 zinc cations. In 2013, Williams et al first reported that heterodinuclear MOF catalysts exhibited evidently higher activity upon the cycloaddition or copolymerization of CO 2 and epoxide than the homodinuclear ones, which might be due to the fact that the combination of chemically dissimilar metals displayed discrepant bimetallic surfaces and a high concentration of regularly distributed Lewis acid sites. So far, although the coexisting secondary building units (SBUs) of {InM 2 }, {In 2 M 2 }, {In 3 Ln}, and {In 3 Ln 2 } are reported, , the oriented strategy of integrating In 3+ 5p and Zn 2+ 3d metal elements into one SBU as inorganic nodes in MOFs has not yet been explored, maybe because the high and multifarious coordination numbers of In 3+ and Zn 2+ ions facially lead to their incompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), constructed of ligands and metal ions/clusters, are a major kind of crystalline metal–organic solid material. MOFs exhibit the characteristic features of the large surface area, controllable structure, modifiable pore size, and so on. The porous natures of MOFs make them promising in the field of heterogeneous catalysts or/and excellent catalyst supports. Thus, high stability in polar solvents and high catalytic activity could be obtained by combining the characteristics of POMs and MOFs, i.e., polyoxometalate-based metal–organic frameworks (POMOFs). ,,,, For example, Liu and co-workers reported a stable POMOF, [Cu I (bbi)] 2 {[Cu I (bbi)] 2 V IV 2 V V 8 O 26 } (bbi = 1,1′-(1,4-butanediyl)­bis­(imidazole)), which could catalyze the oxidative cleavage of lignin efficiently .…”
Section: Introductionmentioning
confidence: 99%